In vitro antibacterial effect of Euterpe oleracea Mart. and Theobroma grandiflorum hydroalcoholic extracts - Sprenger, Lew Kan; Giese, Elane Guerreiro; dos Santos, Jeannie Nascimento; Molento, Marcelo Beltrão (Archives of Veterinary Science, 2016)
This study evaluated the in vitro antimicrobial activity of these species against strains of Gram-positive and Gram-negative bacteria. The hydroalcoholic extracts were prepared from dried leaves, pulp and seeds of E. oleracea Mart. and T. grandiflorum by continuous percolation with 70% ethyl alcohol. The antimicrobial activity was evaluated against four microorganisms by the agar disc diffusion method and the minimal inhibitory concentration (MIC) assay. The antimicrobial activity showed that the açai pulp and seeds possessed significant inhibition in Clostridium perfringens (320 and 640 MIC), Staphylococcus aureus (80 and 320 MIC) and Pseudomonas aeruginosa (640 and 2560 MIC). Cupuassu extracts showed no effect on any bacteria. The use of açai extract products can be a sustainable, viable and an accessible alternative for antimicrobial treatment. New studies should be conducted to determine better results for acai herbals and new formulations of cupuassu extracts.